2018
DOI: 10.1097/nne.0000000000000489
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Clinical Judgment of Prelicensure Nursing Students in the Clinical Setting

Abstract: Assessing clinical judgment for safe nursing practice is a challenge. In this study, the Lasater Clinical Judgment Rubric (LCJR) was used to evaluate clinical judgment of junior and senior nursing students in the clinical setting. Juniors demonstrated an accomplished level on the total scale and all 4 subscales, whereas seniors had exemplary clinical judgment on the total scale and 3 of 4 subscales. The study provides evidence in support of the use of the LCJR to assess students' clinical judgment in the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…The development of clinical judgment in nursing students entails simulation teaching. As nursing students have not yet acquired sufficient judgment and skills, allowing them to practice in real clinical settings can cause tremendous concerns from patients [6]. Benner [7] found that it often takes one or 2 years of clinical experience for a novice nurse to become an expert.…”
Section: Introductionmentioning
confidence: 99%
“…The development of clinical judgment in nursing students entails simulation teaching. As nursing students have not yet acquired sufficient judgment and skills, allowing them to practice in real clinical settings can cause tremendous concerns from patients [6]. Benner [7] found that it often takes one or 2 years of clinical experience for a novice nurse to become an expert.…”
Section: Introductionmentioning
confidence: 99%
“…A 2018 study evaluating junior-and senior-level undergraduate nursing students allowed for multiple opportunities to assess student performance in the clinical setting and found senior students had a statistically significantly higher mean score than juniors. This is evidence that clinical judgment can be assessed in the students' clinical experiences (Manetti, 2018). The authors acknowledge more studies are needed to confirm validity of the tool in the clinical setting.…”
Section: Clinical Reasoningmentioning
confidence: 79%
“…Simulation is a type of experience‐based learning method that has been utilized to improve clinical competence. NGRNs lack the clinical judgment needed to adapt to the clinical environment (Manetti, 2018). This study compared the impact of three different learning modalities (HFS, VS, or CS) on NGRNs' clinical judgment and perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…The terms “clinical judgment,” “clinical reasoning,” “critical thinking,” and “decision making” are often used interchangeably (Brown Tyo & McCurry, 2019). Clinical judgment is well recognized as a necessary ability for NGRNs to effectively cope with today's demanding clinical care environment and transform into clinical experts (Goudreau et al, 2015; Lee et al, 2017; Manetti, 2018). A previous study pointed out that in addition to gaining essential clinical judgment, building confidence is key to successful role transitions for NGRNs (Powers et al, 2019).…”
Section: Introductionmentioning
confidence: 99%